IMPACTO DE LA INTENSIDAD DE PASTOREO EN EL VIGOR Y PESO DE Festuca humilior (NEES & MEYEN) Y Calamagrostis vicunarum (WEDDELL) - Aguirre, Lucrecia (2024)
The tussock grasslands of Festuca humilior (Nees & Meyen) and Calamagrostis vicunarum (Weddell) have a significant extension in the Central Andes and are considered a recognized vegetation association for its ecological-economic value. The objective of this research was to estimate the cumulative impact of the level of use of the key grasses F. humilior and C. vicunarum on height, vigor and weight of the plant. The study was carried out in a humid grassland of regular condition located 4 186 masl in the Puna ecoregion. The variables evaluated were: plant height, basal and canopy diameter and plant weight. The experiment lasted two years during which individual plants of each species were cut every four months. The vigor was estimated from the volume (cm3) and the weight of the plant (gMS/plant) from the regression of the weight and the volume of the plant. Height (cm) was the length from the soil surface to the flag leaf. The experimental design was a randomized block design with a 2x3 factorial arrangement, two species and three height removal levels: zero, 40 and 80%. The height, vigor and weight of F. humilior and 1 vicunarum were reduced in response to increasing use level, but the changes were more marked in Festuca than in Calamagrostis. While the decrease in the evaluated variables was constant for F. humilior as the level of use increased, Calamagrostis also decreased, but to a lesser extent, remaining almost constant when biomass removal levels changed from moderate to heavy, suggesting that this species is more grazing tolerant. The results found help to explain why in fields dominated by F. humilior and sub-dominated by C. vicunarum subjected to intense grazing, dominance relationships change in favor of C. vicunarum, a species of lower forage value than F. humilior.